2021
DOI: 10.21776/ub.ijhn.2021.008.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Nutritional Status of Javanese Women in Rice Producing Areas: a Comparison between Lactating and Non-lactating Women

Abstract: <p>Maintaining optimal maternal nutrition is essential for the mother’s health and the child’s growth and development. Throughout the lactating period, maternal nutrition is significant due to the child’s high nutritional needs. Therefore, an increase in food consumption is necessary. This research aimed to analyze the dietary intake and nutritional status of lactating and non-lactating women living in rice-producing areas in Central Java, Indonesia. A cross-sectional study was conducted from December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This habit may lead the lactating women in this region to have low dietary quality and diversity, low protein consumption as well as low consumption of fruits and vegetables. This trend is also observed among European and Urban Chinese lactating women ( 23 , 24 ). This trend of dietary pattern may affect the nutrient adequacy of pregnant and lactating women and will further influence maternal and child nutrition and health outcomes.…”
Section: Introductionsupporting
confidence: 56%
“…This habit may lead the lactating women in this region to have low dietary quality and diversity, low protein consumption as well as low consumption of fruits and vegetables. This trend is also observed among European and Urban Chinese lactating women ( 23 , 24 ). This trend of dietary pattern may affect the nutrient adequacy of pregnant and lactating women and will further influence maternal and child nutrition and health outcomes.…”
Section: Introductionsupporting
confidence: 56%
“…A study in Bogor Indonesia showed that the lactating mothers' nutritional status was lower than the pre-pregnant women's nutritional status (37). Another study in Indonesia also showed that the nutritional status of lactating women was lower compared to the women who were not lactating (38). Fikawati et al's study in Java Island, Indonesia, also showed that the energy consumption of lactating women was low (39).…”
Section: Discussionmentioning
confidence: 99%